Pengaruh burnout terhadap kinerja tenaga kesehatan di Puskesmas Kresek Kecamatan Kresek Kabupaten Tangerang tahun 2023 - Ade Fauzi (Vanchapo Health Science Journal, 2023)
The World Health Organization (WHO) defines Burnout to describe chronic stress conditions related to work. Health workers are at risk of experiencing burnout by 54.1% due to lack of knowledge, high workload, and several other factors at work. Research purposes. Analyzing the effect of Burnout on the performance of health workers at the Kresek Health Center, Kresek District, Tangerang Regency in 2022. Research methods. The type of research conducted is quantitative research with a correlation approach, namely looking at the relationship between burnout and the performance of health workers. The research design used in this study was cross sectional. The research data used primary data by filling out questionnaires. The collected data was then computerized and processed using the Spearman Rho statistical technique. ResultsStudy. The results showed that most of the 62 respondents had high burnout, namely 45 respondents (72.6%) and most of them also had poor health worker performance, namely 43 respondents (69.4%). The results of the Spearmen's Rho statistical test showed that the p value = 0.632 which means greater than 0.05 (p <α ) so it can be concluded that there is no significant effect between burnout and health worker performance. Conclusions and recommendations. No impactbetween burnout on the performance of health workers at the UPTD Puskesmas Kresek, Kresek District, Tangerang. This research is expected to be input for the puskesmas to conduct research for health workers in an effort to reduce/increase burnout and good performance of health workers, especially health workers.